PENGARUH CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN PADA MOTOR SUZUKI SATRIA FU 150 - Ahmad Tarmizi (Universitas Batanghari Jambi, 2014)
Two-wheeler automotive industry that still exist in the market, it must remain consistent with the strategy to understand the wants, needs and tastes of consumers. Strategies that can be used by automotive companies is the strategy of branding and increase product quality. PT.Angsana Indah Jaya is a company engaged in the sale of automotive products. In the automotive field, the company markets products Suzuki motorcycle which is the top brand of the company 'from Japan, and PT.Angsana Jaya Indah is located in the city of Jambi. In this study, the author uses primary data. For the calculation of the statistics the authors use a computer program IBM SPSS The analysis tool used is a simple linear regression equation, test the coefficient of determination (R2), and t test. PT Angsana Jaya Indah was founded in 2010 in Jambi. Indah Jaya is a branch perusaan with the Suzuki brand as a product marketed both in terms of motor vehicles and four-wheeled vehicles. Based on the results of the study respondents agreed with Brand Image product Suzuki Satria fu 150 PT. Angsana Jaya Indah branch Jambi with the average score of 358. With the regression equation Y = 0,987 + 0,727X + e. thus it can be concluded that the regression Brand Image has a positive direction on purchasing decisions Suzuki Satria Fu 150 on PT.Angsana Jambi Jaya branch. Based on the analysis of Likert scale Brand Image and influence the consumer's decision to buy all provide value to agree, so of all the variables studied had a good outcome or conclusion agrees. And Based on the research results prove that the variable Brand Image is effect on consumer purchasing decisions.